Social Media and Social Networking's Impact on Consumers - Frans Sudirjo; I Nyoman Tri Sutaguna; Rini Hadiyati; Syamsu Rijal; Geofakta Razali (STIE AMKOP, 2023)
The pandemic has had a big effect on the world, not just negatively but also in a lot of different industries. One of these sectors is the sports industry, where one of the results has been the increase in basketball tournaments, which inexorably has an effect on basketball-related products such specialized clothing. This product fills a niche in the market that the general public barely knows about because of its function, variety, and high level of product quality. During pandemics when social activities are restricted, this information search activity transfers to the network and involves visiting social media and social networking sites to learn more about products. Data for this qualitative study came from 141 respondents in Garut who play basketball regularly. The data was analyzed using SPSS, and it was found that social networks and social media have a big impact on people's decisions to buy basketball-related clothes. Kata Kunci: Media Social , Networking Social , Decision Purchase